Effects on vessel measurement accuracy and subsequent occlusion after calcium channel blocker infusion during treatment of cerebral aneurysms with the Pipeline embolization device. Issue 1 (February 2017) - Alexander, MD; Nicholson, AD; Darflinger, RJ; Settecase, F; Cooke, DL; Dowd, CF; Amans, MR; Higashida, RT; Hetts, SW; Halbach, VV
Introduction/Purpose: To achieve aneurysm occlusion, flow diverters (FDs) must be accurately sized to maximize coverage over the neck and induce thrombosis. Catheterization for diagnostic angiography can cause vasospasm that may affect vessel measurements. This study evaluates impacts of intra-arterial infusion of a calcium channel blocker (CCB) on angiographic measurements in patients treated with FDs to determine effects on final diameter of the FD and subsequent occlusion. Materials and methods: Pre-treatment measurements were recorded for diameter of the distal and proximal landing zones and maximum and minimum diameters between these segments. Post-treatment measurements of the stent following deployment were recorded at these locations. When CCB was infused, post-infusion pre-treatment measurements were recorded. Rates of occlusion were noted for all patients. T -tests were performed to assess for differences in pre- and post-treatment measurements and rates of occlusion between groups with and without CCB infusion. Results: Twenty-eight FDs were deployed to treat 25 aneurysms in 24 patients. CCB infusion was performed prior to deployment of 12 (42.9%) devices. No significant difference was noted between groups for pre- and post-treatment measurement changes. Confirmed aneurysm occlusion was more likely to occur in the CCB infusion group (88.9% vs. 36.4%, p = 0.009). Conclusion: Optimization of device sizing is important to increase FD density over the aneurysm neck and promote thrombosis. To improve measurement accuracy, CCB infusion can reduce effects of mild vasospasm. Subsequent aneurysm occlusion was more likely to occur following FD treatment when device size selection was based on measurements performed following CCB infusion.